2020
DOI: 10.1177/1350650120940173
|View full text |Cite
|
Sign up to set email alerts
|

Lubrication mechanisms of hexagonal boron nitride nano-additives water-based lubricant for steel–steel contact

Abstract: This study intends to explore the lubrication mechanism of hexagonal boron nitride nano-additive. Synergistic analysis comprising worn surface observation, surface wettability testing, and the Stribeck curve principle is used to test this water-based lubricant on steel–steel contact. Distilled water and 0.1–5.0 vol.% hexagonal boron nitride nano-additive is used to prepare a mixture using sonification technique. A viscometer is employed to determine the viscosity of the nanolubricant. A four-ball trib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 29 publications
(44 reference statements)
1
22
0
Order By: Relevance
“…However, when mass fractions of CNOs in the CSCG‐FG exceeds 0.10 wt%, the aCoF increased with the increase amounts of CNOs , which may be due to the agglomeration of CNOs 14 and resulted in the increase of abrasive wear 19,27 . This has also been reported in the other literatures 43–45 …”
Section: Discussionsupporting
confidence: 68%
“…However, when mass fractions of CNOs in the CSCG‐FG exceeds 0.10 wt%, the aCoF increased with the increase amounts of CNOs , which may be due to the agglomeration of CNOs 14 and resulted in the increase of abrasive wear 19,27 . This has also been reported in the other literatures 43–45 …”
Section: Discussionsupporting
confidence: 68%
“…Wei et al [34] prepared GO/chitosang-PNIPAM nanohybrids by combining GO and brush-like chitosan-based copolymer (chitosan-graftpoly (N-isopropylacrylamide), chitosan-g-PNIPAM) for water-based lubrication and found that it reduced the average COF by 40% compared to raw GO and by 84% compared to a single copolymer, and reduced wear rates by 15% and 47%, respectively. Bin Abdollah et al [35] proposed that increasing the amount of hexagonal boron nitride additive may cause the lubricating state to change from mixed lubrication to hydrodynamic, allowing nanoparticles to aggregate, resulting in increased friction. Liu et al [36] found the surface modification endowed SiO 2 with smaller particle size and better dispersibility, significantly reduced the wear of SiO 2(TESPT) /NBR.…”
Section: Additives In Water-based Lubricationmentioning
confidence: 99%
“…Meanwhile, it can generate a boron oxide (B 2 O 3 ) friction chemical film by friction chemical reaction. Abdollah et al [ 78 ] found that h-BN can significantly improve the lubricating properties of pure water, and the appropriate increase in h-BN concentration can change the lubrication state of water-based lubricants from mixed lubrication to hydrodynamic lubrication. Ma et al [ 79 ] successfully exfoliated a flake nanosheet h-BN with 100 nm ultrathin thickness from a block h-BN and compared the effects of the two forms of h-BN on the lubricating properties of base oils.…”
Section: Single Nanoadditivementioning
confidence: 99%